Synthesis of Optical Circuits Using Binary Decision Diagrams - Deb, Arighna; Wille, Robert; Keszocze, Oliver; Shirinzadeh, Saeideh; Drechsler, Rolf (Integration-The Vlsi Journal, 2017)
The advances in silicon photonics motivated the consideration of optical circuits as a new and emerging circuit technology. In particular for ultra-fast interconnects, optical circuits may provide a suitable alternative since it avoids the conversion of signals from the optical to the electrical domain. Accordingly, design automation of this kind of circuits received significant attention. In this work, we consider synthesis of optical circuits based on Binary Decision Diagrams (BDDs). Although BDDs allow for a direct mapping of the function representation to an optical circuit (and, hence, a scalable synthesis), they have their shortcomings with respect to dedicated cost metrics. In this work, we investigate this issue and provide an overview of the BDD-based synthesis schemes which are available thus far. Afterwards, we propose new solutions based on a dedicated BDD optimization which aim for addressing the known shortcomings. Experimental results confirm the benefits of the proposed approach.
Keywords: Optical circuits; Synthesis; Optimization; Binary decision diagrams